(untitled) (Al Dzahab, 2024)
Purpose: This study aims to determine the effect of inflation and interest rates on financing at Islamic banks in Banjarmasin city. Design/methodology/approach: This research uses quantitative methods. The data used is secondary data and time series. Data sourced from the pages of Bank Indonesia, the Financial Services Authority (OJK), the Central Statistics Agency (BPS) and data from Islamic Commercial Banks which are the objects of this study in the period 2014 to 2023. Findings: Based on the results of statistical data processing, the results of this study indicate that the value of Sig. Inflation variable (X1), amounting to 0.993> 0.05 and the tcount value of 0.009 < 2.571. Sig value. Interest Rate Variable (X2) is 0.066> 0.05 and the tcount value is -2.571 < 2.571. The results of this study indicate that simultaneously the inflation and interest rate variables affect financing at Islamic banks in Banjarmasin City. This can be proven by the value of Fcount 2.825 > Ftable 4.45. Research implications: Based on the research results, it is known that although inflation and interest rates have no effect on financing in Islamic banks, the government must remain effective in controlling macroeconomic activities to maintain the stability of inflation and interest rates, so that economic stability can be guaranteed.